Nutritional Extremes and the Paediatric Heart: A Critical Narrative Review of Deficiency Cardiomyopathy and Obesity-Related Cardiac Remodelling - Ashraf Soliman; Anas AbdulKayoum; Mohanad M. A L-Qadi; Fawzia Alyafei; Shayma Ahmed; Consultant Noora AlHumaidi; Nada Alaaraj; Noor Hamed (Journal of Advances in Medicine and Medical Research, 2026)
The developing heart is unusually exposed to the nutritional environment because it must sustain a continuously rising cardiac output while its own mass, metabolic machinery and extracellular matrix are still being assembled. Both ends of the nutritional spectrum leave a cardiac signature in childhood, yet the two literatures have developed largely in isolation: deficiency cardiomyopathy has been described mainly through case series and small hospital cohorts in low- and middle-income settings, whereas obesity-related remodelling has been characterised through imaging studies in high-income populations. This critical narrative review examines what can defensibly be concluded from the two bodies of evidence when they are appraised against one another. Sources were identified through structured searching of PubMed, Europe PMC, Crossref, OpenAlex, the Directory of Open Access Journals, Semantic Scholar, Google Scholar and African Journals Online, supplemented by citation searching and by documents from intergovernmental agencies, for the period 1990 to 19 June 2026. The synthesis indicates that micronutrient deficiency states produce mechanistically distinct and, in several cases, rapidly reversible cardiomyopathies whose reported reversibility rests almost entirely on uncontrolled observation. In severe acute malnutrition the dominant finding across echocardiographic series is reduced left ventricular mass with preserved systolic function and variable diastolic impairment, a pattern that conflicts with the long-standing clinical assumption of a failing malnourished myocardium and that has direct implications for fluid management. At the opposite extreme, adiposity is consistently associated with increased left ventricular mass, adverse geometry and impaired longitudinal deformation from as early as eight years of age, with effect estimates tracking fat mass more closely than metabolic phenotype. Interpretation across both fields is constrained by inconsistent body-size indexation, cross-sectional design, small samples and near-total absence of hard cardiac endpoints in childhood. Priorities include indexation standards independent of the exposure, prospective cohorts spanning nutritional transition, and reversibility studies with predefined cardiac endpoints.